A prospective randomised study on narrow-band imaging versus conventional colonoscopy for adenoma detection: does narrow-band imaging induce a learning effect?. Issue 1 (6th August 2007) - Adler, A; Pohl, H; Papanikolaou, I S; Abou-Rebyeh, H; Schachschal, G; Veltzke-Schlieker, W; Khalifa, A C; Setka, E; Koch, M; Wiedenmann, B; Rösch, T
Abstract : Background and aims: Colonoscopy is an established method of colorectal cancer screening, but has an adenoma miss rate of 10–20%. Detection rates are expected to improve with optimised visualisation methods. This prospective randomised study evaluated narrow-band imaging (NBI), a new technique that may enhance image contrast in colon adenoma detection. Methods: Eligible patients presenting for diagnostic colonoscopy were randomly assigned to undergo wide-angle colonoscopy using either conventional high-resolution imaging or NBI during instrument withdrawal. The primary outcome parameter was the difference in the adenoma detection rate between the two techniques. Results: A total of 401 patients were included (mean age 59.4 years, 52.6% men). Adenomas were detected more frequently in the NBI group (23%) than in the control group (17%) with a number of 17 colonoscopies needed to find one additional adenoma patient; however, the difference was not statistically significant (p = 0.129). When the two techniques were compared in consecutive subgroups of 100 study patients, adenoma rates in the NBI group remained fairly stable, whereas these rates steadily increased in the control group (8%, 15%, 17%, and 26.5%, respectively). Significant differences in the first 100 cases (26.5% versus 8%; p = 0.02) could not be maintained in the last 100 cases (25.5% versus 26.5%, p = 0.91). Conclusions: The increased adenoma detection rate means of NBI colonoscopy were statistically not significant. It remains speculative as to whether the increasing adenoma rate in the conventional group may have been caused by a training effect of better polyp recognition on NBI.